Consumer Protection Strategies through Legal and Management Perspectives in the Era of Voice Cloning - Ummah, Siti Risdatul; Palupi, Nur Wulan Intan (Institut Bisnis dan Informatika Kesatuan, 2024)
The advancement of artificial intelligence technology, especially voice cloning, opens up opportunities for innovation while also presenting new risks in digital marketing. This study explores the potential for misuse of this technology to manipulate consumers through false promotions, using a legal and management perspective. Using a normative legal approach and literature study, this study analyzes regulations in Indonesia, such as the Information and Electronic Transactions Law, the Consumer Protection Law, and the Personal Data Protection Law, and compares them with practices in other countries. The results of the study indicate that regulations in Indonesia are not yet adequate to handle the complexity of voice cloning misuse, especially in consumer and personal data protection. Therefore, companies are advised to adopt strategies such as utilizing detection technology, increasing consumer digital literacy, and implementing stronger internal policies. This study highlights the importance of updating regulations that are more responsive to technological developments, including voice cloning. In addition, cross-sectoral collaboration between the government, industry players, and the community is key to protecting consumers while utilizing the potential of voice cloning technology responsibly and ethically.